PositioningAsian Australian Writing: A Study of Three Australian Literary Anthologies - Ramlan, Wan Nur Madiha; Abdul Kadir, Maimunah (2021)
This paper examines three anthologies of Australian literature: The Oxford Anthology of Australian Literature (1985), The Macmillan Anthology of Australian Literature (1990),and Macquarie PENThe Anthology of Australian Literature (2010).It focusses on the politics of inclusion in anthology-making and the mechanics surrounding theme, perception, and ideology about literature as a reflection of a nation’s culture and identity.The increasing popularity of Asian Australian writing in recent years has raised concerns about how it is perceived as part of the national literary tradition that is a relatively white space. Not much is discussed about how Asian Australian writing appears in anthologies despite increasing critical attention given to them as a literary genre. Informed by Asian Australian studies and anthology criticism, this study charts the trends in the inclusion of Asian Australian writing and how it is posited within the larger national canon